Integrating Higher-Order Thinking Skills into PBL Modules to Enhance Students’ Critical Thinking Skills - Oktha Ika Rahmawati; Meiga Ratih Tirtanawati; Ma'rifatul Ain; Listiana Wati (Jurnal Pendidikan Edutama, 2026)
Grammar mastery is essential in English as a Foreign Language (EFL), particularly for academic contexts such as TOEFL. However, the increasing use of artificial intelligence (AI) in grammar learning risks encouraging surface-level accuracy without deep cognitive engagement. This study aimed to develop a Higher-Order Thinking Skills (HOTS)-based grammar learning module focusing on clause mastery by integrating Problem-Based Learning (PBL) within the ADDIE instructional design model. Using a Research and Development (R&D) approach, the study followed five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation and student questionnaires and analyzed using descriptive quantitative and qualitative methods. The material expert evaluation showed a feasibility score of 84.6% (highly feasible), while student responses indicated a feasibility level of 78.8% (feasible). Students perceived the module as effective in enhancing analytical and evaluative thinking. The findings suggest that the HOTS-based grammar module is pedagogically feasible and supports deeper cognitive engagement in grammar learning, provided it is implemented with coherent instructional strategies and appropriate assessment alignment in AI-supported learning environments.